Decadal modulation of East Asian summer monsoon variations by external forcing and internal variability. (1st October 2022) - Zhu, Junji; Zhao, Kan; Wang, Yongjin; Cui, Yingfang; Liang, Yijia; Cheng, Hai; Edwards, R. Lawrence; Kong, Xinggong; Shao, Xiaohua; Chen, Shitao; Pang, Lin
Abstract: Both external forcing and internal climate variability are playing significant roles in driving the East Asian summer monsoon (EASM) changes. However, dynamic linkages between these natural forcings and EASM on decadal timescales remain uncertain, partly due to the limited instrumental climate data. Here, we present a high-resolution EASM record over the past 200 years based on 2315 δ 18 O measurements from two annually laminated stalagmites (YX92 and YX120) in Yongxing Cave over the middle Yangtze River Valley (mid-YRV). Our records match well with the δ 18 O records from the nearby Heshang Cave, showing that EASM intensity in the mid-YRV varies at a dominant periodicity of ∼80 years. The multidecadal-scale oscillations in the EASM intensity are closely related to the ENSO-like states, supporting a notion that the ENSO dominantly modulates the EASM variability. Furthermore, the decadal oscillations in EASM and ENSO are synchronous with tropical volcanic eruptions during the solar minima, probably leading to the enhanced El Niño-like response, intensified EASM and strengthened ENSO-EASM coupling. Our findings imply that external forcings potentially contribute to the anomalies in ENSO and EASM during the ongoing global warming. Highlights: EASM changes at a dominant periodicity of ∼80 years over the past 200 years. Multidecadal-scale oscillations in EASM intensity closely related to ENSO-like states. Decadal oscillations in EASM and ENSO evolution synchronous with tropical volcanic eruptions during the solar minima. Tropical volcanic eruptions likely enhanced the ENSO-EASM coupling.